Hypermarket Competition and the Diffusion of Retail Checkout Barcode Scanning - Jonathan Beck; Michał Grajek; Christian Wey (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
This paper presents a set of panel data to study the diffusion of retail checkout barcode scanning in ten European countries over the period 1981-1996. Estimates from a standard diffusion model suggest that countries differ most in the long-run diffusion level of barcode scanning and less in timing or diffusion speed. We present evidence that the emergence of hypermarkets raises competitive intensity and use hypermarket data, among other variables, in a pooled estimation. Results suggest that hypermarket competition reduces long-run adoption of information technology (IT) in retailing. In particular, the emergence of hypermarkets seems to deepen retail segmentation by inducing potential adopters (e.g. supermarkets) to exit the market and/or by discouraging adoption by other retail formats. Consistent with expectations, scale and income effects spur IT diffusion and there is a classic substitution effect: when wages rise, diffusion of a labor-saving technology such as barcode scanning is more intense. We do not find a significant impact of employment protection legislation.
Keywords: O33; L81; L5; 330; IT diffusion; retail competition; hypermarkets; Barcode; Einzelhandel; SB-Center; Wettbewerb; Innovationsdiffusion; Panel; EU-Staaten